Inter-laboratory verification of European pharmacopoeia monograph on derivative spectrophotometry method and its application for chitosan hydrochloride - Marković, Bojan; Ignjatović, Janko; Vujadinović, Mirjana; Savić, Vedrana; Vladimirov, Sote; Karljiković-Rajić, Katarina (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2015)
Derivative spectrophotometry – interlaboratory method transfer in pharmaceutical analysis. [Display omitted] •Inter-laboratory verification of derivative spectrophotometry method-EP monograph.•Resolution power–amplitude A/B ratio through instrumental and algorithm’s parameters.•Algorithm’s parameter smoothing points (SP) 7 required for verification.•Chitosan hydrochloride-degree of deacetylation (1D202; SP 9; 2nd polynomial degree).•Accepted criteria up to 2% or 3% between averages for method transfer. Inter-laboratory verification of European pharmacopoeia (EP) monograph on derivative spectrophotometry (DS) method and its application for chitosan hydrochloride was carried out on two generation of instruments (earlier GBC Cintra 20 and current technology TS Evolution 300). Instruments operate with different versions of Savitzky–Golay algorithm and modes of generating digital derivative spectra. For resolution power parameter, defined as the amplitude ratio A/B in DS method EP monograph, comparable results were obtained only with algorithm’s parameters smoothing points (SP) 7 and the 2nd degree polynomial and those provided corresponding data with other two modes on TS Evolution 300 Medium digital indirect and Medium digital direct. Using quoted algorithm’s parameters, the differences in percentages between the amplitude ratio A/B averages, were within accepted criteria (±3%) for assay of drug product for method transfer. The deviation of 1.76% for the degree of deacetylation assessment of chitosan hydrochloride, determined on two instruments, (amplitude 1D202; the 2nd degree polynomial and SP 9 in Savitzky–Golay algorithm), was acceptable, since it was within allowed criteria (±2%) for assay deviation of drug substance, for method transfer in pharmaceutical analyses.